Oil-water relative permeability data for reservoir simulation input, part-1: Systematic quality assessment and consistency evaluation - Agnia, A. (Society of Petroleum Engineers, 2014)
The relative permeability concept has been used extensively in reservoir engineering. As numerical reservoir simulation has become more popular as a tool for reservoir development, the role of relative permeability data became even more evident and important. Its key use is to control the advancement and mobility of different fluids simultaneously coexisting in the porous media, and hence controlling the recovery of the fluids. However, deriving a reliable relative permeability data set remained a major challenge. In reservoir engineering, this challenge has been present for many decades and might be so in the foreseeable future. Another challenge is to have a data set which is internally consistent and does not hinder the simulation performance. Optimistically, with the significant literature accumulated over the years in deriving and using relative permeability, some techniques can be extracted for data quality check, control and assurance. This paper covers the limitations of the conventional methods used for calculating relative permeability from displacement experiments. It also compiles all contemporary techniques in a systematic workflow for quality assessment and consistency evaluation. The workflow has been demonstrated with different synthetic and field examples. This paper will provide a reference for reservoir engineers who have an interest in investigating, checking the quality, and preparing relative permeability data set usable for reservoir simulation process. Copyright Â© 2014, International Petroleum Technology Conference.